THESMOPHORIA - Başak Emir (Journal of Ancient History and Archaeology)
Ancient Age women were in a social order in which they do not have any legal rights nor a social status. On the contrary, these women are also at the forefront in the religious activities. Even some cults were exclusively open for only women. The best example for this is the rituals, which were done in the name of Demeter. The name of Goddess of Earth and fertility –Demeter- originates from the “Gemeter” that means the Mother Earth. She is from the second generation of gods and goddesses and daughter of Kronos and Rhea. The offspring of her relationship with Zeus who is also her brother is called Kore or Persephone. In the structural context, Demeter is a derivation of Earth and fertility goddesses of Neolithic times. The Daughter of Demeter Kore-Persephone was kidnapped by Hades and became the Goddess of underworld. The original name of the goddess was Kore, which means the “daughter”. Hades named her “Persephone” after she became the goddess of the underworld. The mysteries’ of the Demeter were taped to the myth of Demeter and her daughter Persephone. The time Demeter remains separated from Persephone was perceived as winter while the time when she meets Persephone was perceived as spring. Thesmophoria is one of the religious rituals, which were organized for Demeter. Swine sacrificing, fast and purifications were the main rituals of Thesmophoria.